2017
DOI: 10.1039/c7py00616k
|View full text |Cite
|
Sign up to set email alerts
|

Naphthodipyrrolidone (NDP) based conjugated polymers with high electron mobility and ambipolar transport properties

Abstract: Conjugated polymers based on NDP were synthesized and characterized. The polymer thin film organic field effect transistor exhibited ambipolar transport properties with an electron mobility up to 0.67 cm2 V−1 s−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Over the past several decades, organic conjugated polymers (CPs) with inorganic silicon‐like semiconducting behaviors have attracted more and more attentions from the scientific community due to their intriguing properties of mechanical flexibility and solution processability. [ 1–4 ] A great material library of new CPs have been established, which together with surface engineering of the device interfacial layers and optimization of device fabrication procedures, have led to significant improvements of device performances in many electronic applications such as organic thin‐film transistors (OFETs), organic solar cells (OSCs), and so on. [ 5–10 ] Among tremendous efforts to elevate their device performances, the material design of new CPs with novel molecular structures and ideal physicochemical properties serves as the cornerstone for the success of the organic electronic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, organic conjugated polymers (CPs) with inorganic silicon‐like semiconducting behaviors have attracted more and more attentions from the scientific community due to their intriguing properties of mechanical flexibility and solution processability. [ 1–4 ] A great material library of new CPs have been established, which together with surface engineering of the device interfacial layers and optimization of device fabrication procedures, have led to significant improvements of device performances in many electronic applications such as organic thin‐film transistors (OFETs), organic solar cells (OSCs), and so on. [ 5–10 ] Among tremendous efforts to elevate their device performances, the material design of new CPs with novel molecular structures and ideal physicochemical properties serves as the cornerstone for the success of the organic electronic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the isoDPP, the BDP, and NDP showed similar chemical structures except the core are tri-and tera-cyclic (Deng et al, 2019). Rumer et al reported BDP based polymers with ambipolar behavior with µ h and µ e of 0.2 and 0.1 cm 2 V −1 s −1 , respectively (Rumer et al, 2013) (Figure 2F), while a similar polymer consisting of NDP based polymer exhibited n-type behavior with µ e of 0.67 cm 2 V −1 s −1 (Zhang et al, 2017b) (Figure 2G). The different properties of these semiconductors could be due to the fact that the π-conjugation extension could not only enlarge the charge transfer pathway, but also adjust the frontier molecular orbitals.…”
Section: Dpp-based Derivativesmentioning
confidence: 84%
“…Soon after, the same group used P47 to construct OFET showing ambipolar semiconducting behavior with a μ h of 0.015 cm 2 V −1 s −1 and an μ e of 0.227 cm 2 V −1 s −1 . In this work, another polymer (P41) using bithiophene as donor unit was synthesized, which showed an μ e of even up to 0.667 cm 2 V −1 s −1 [83]. The charge carrier mobility was only one order magnitude lower when the device was exposed in air after one week.…”
Section: Polymersmentioning
confidence: 99%